Application of Scientific Approach-Based Learning Assisted by Question Cards and Ladder Snake Media for Evaluating Learning Outcomes - Sio Tuti Gultom; Rafles Sinaga; Ramlan Silaban (Postgraduate, University of Mataram, 2023)
This study aims to determine the differences in student learning outcomes by applying to learning using question cards and snakes and ladders media through a scientific approach to the topic of acid-base discussion. Ultimately, the evaluation of improving the learning outcomes of students by learning using question cards and ladder snake media through a scientific approach to the topic of acids and bases is reported in this study. The population in this study were all students of class XI MS SMA Negeri 20 Medan, total three classes. The sample was taken by purposive sampling in two classes. The first class was experimental I, taught using a scientific approach using question cards, and the second class was experimental class II, conducted using a scientific approach using snakes and ladders. Each experiment class consists of 32 students. The research instrument was a multiple choices objective test instrument of 25 questions which had been tested for validity, reliability, discriminating power, and level of difficulty for learning outcome data. Test the first hypothesis using a two-party t-test, and SPSS 21 (independent samples t-test) results obtained for experimental class I with a tcount value of 32.320 > ttable 1.70. In contrast, the experimental class II has a tcount value of 31.231 > ttable 1 .70 at a significance level of 0.000 < 0.05. The second hypothesis test using the proper side t-test and in SPSS 21 (paired samples t-test) obtained a mean of 5.000 and a t-test value of 2.648 with a sig value of 0.010 <0.05.